2014
DOI: 10.15835/nbha4229632
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Comparative Regulation on Antioxidant Enzyme System under Copper Treatment and Drought Stress in Maize (<i>Zea mays</i> L.)

Abstract: The present study was conducted to present the responses of drought-sensitive ‘Shemal’ and drought-tolerant ‘71MAY69’ maize cultivars under drought condition (20% Polyethylene glycol, -0.40 MPa) and three different copper concentrations (0.5 mM, 1 mM, 1.5 mM CuSO4.5H2O) for 5 days to determine the enzymatic responses of copper treatment in maize leaves.Copper treatments alone did not change stomatal conductance, relative water content, malondialdehyde, proline, hydrogen peroxide content and abscisic acid level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 43 publications
1
5
0
Order By: Relevance
“…However, a non-significant increase with an increase in soil-applied cellulolytic-enriched vermicompost rates was also recorded for some traits. Similar to that, previous studies also showed that drought-stressed plants had higher canopy temperatures than non-stressed ones (Azarmi et al, 2008;Bowden et al, 2010;Cetinkaya et al, 2014;and Bai and Purcell, 2018). The highest canopy temperature was recorded in plants without vermicompost application under severe drought stress (30% FC) in both cultivars.…”
Section: Discussionsupporting
confidence: 86%
“…However, a non-significant increase with an increase in soil-applied cellulolytic-enriched vermicompost rates was also recorded for some traits. Similar to that, previous studies also showed that drought-stressed plants had higher canopy temperatures than non-stressed ones (Azarmi et al, 2008;Bowden et al, 2010;Cetinkaya et al, 2014;and Bai and Purcell, 2018). The highest canopy temperature was recorded in plants without vermicompost application under severe drought stress (30% FC) in both cultivars.…”
Section: Discussionsupporting
confidence: 86%
“…Water-stressed plants showed a significant decrease in RWC in comparison to other treatments. Many studies showed that water stressed plants had lower RWC than non-stressed ones (Vassileva et al, 2011;Cetinkaya et al, 2014;Gulen et al, 2018). The highest reduction was recorded in plants without VC under severe DS (25% FC) (Fig.…”
Section: Physiological Parametersmentioning
confidence: 96%
“…1D). Important effects of DS on plants includes the decrease in leaf water potential and turgor loss, closure of stomata and decrease in internal CO2 concentration and CO2 assimilation (Rahbarian et al, 2011;Cetinkaya et al, 2014). VC limits stomata closure and increases CO2 supply necessary for photosynthesis due to fact that it has highly porous texture and high capacity for ventilation, proper drainage and water storage (Arancon et al, 2004).…”
Section: Physiological Parametersmentioning
confidence: 99%
“…Cu is micronutrient that is important in plant metabolism like photosynthesis, respiration, protein and carbohydrate metabolism (Horvarth, 1990;Cetinkaya et al, 2014). The results of soil analysis show 3-20 ppm and that is low Cu content.…”
Section: Resultsmentioning
confidence: 99%